Wewenang Pembuatan Akta Tanah oleh Notaris dalam Prespektif Kepastian Hukum - Wahyudi, Bagus Leo (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
One of the authorities given to a notary as a public official is to create authentic deeds, in addition to other powers determined by law. According to Article 1868 of the Civil Code, an authentic deed is one made by an authorized official in a form specified by law. Both notaries and PPAT (Land Deed Officials) have the authority to create land deeds in accordance with applicable regulations. They play crucial roles and bear significant responsibilities in property transactions, ensuring the validity and legal force of these documents. This research employs a normative legal research method, which examines legal norms. The author aligns with Peter Mahmud Marzuki's view that legal research, or Dutch *rechtsonderzoek*, is inherently normative. Legal research involves searching for and uncovering hidden truths. Based on the discussion, and referring to the source of authority for Notaries through Article 15 paragraph (2) of UUJN, a Notary's authority in creating land deeds should be considered attribution or genuine authority. However, in practice, Notaries cannot make land deeds in the same manner as PPAT because PPAT is a partner of BPN (National Land Agency), posing the biggest limitation for Notaries in creating land deeds. For a Notary to create a land deed, they must hold the same position as a PPAT and obtain permission as a PPAT. Among the eight types of land deeds mentioned in Article 2 paragraph (2) of Government Regulation Number 37 of 1998 concerning PPAT Position Regulations, deeds that can be made by a Notary include, among others, the Deed of Sale and Purchase Agreement and the Deed of Power of Attorney to Sell, with the object being land, and the Power of Attorney to Encumber Mortgage Rights (SKMHT). These deeds may be made by a Notary, but their creation must adhere to the laws and regulations governing each position.